Curcumin alleviates deep tissue pressure injury in mice - LIU Pan-pan, ZHANG Zi-rui, YANG Xu, HAN Jing, LU Lian-fang, WANG Ai-min, ZHANG Ju (Jichu yixue yu linchuang, 2020)
Objective To evaluate the effect of curcumin on wound healing in deep tissue pressure injury(DTPI) induced by ischemia-reperfusion in mice. Methods Mice were randomly divided into control group (Con), model group (Mod), 4 and 8 mg/kg curcumin treatment group (Cur 4, Cur 8), 10 mice in each group. A deep tissue pressure injury model was established by magnet compression. The wounds tissue was injected with curcumin every 48 hours and photographed to observe the wound healing. HE staining was used to observe the pathological changes of wound healing. Real-time PCR was used to detect the mRNA expression of TNF-α, IL-6, IL-10, VEGF-α and TGF-β. Western blot was used to detect the expression of VEGF-α, TGF-β, Stat3 and p-Stat3. Results Compared with the control group, the wound in the model group gradually deteriorated, and the pathological changes were obvious. Compared with the model group, the wound healing of the Cur 8 group was significantly accelerated (P＜0.05). Compared with the model group, the inflammatory cell infiltration was reduced and the neovascular density was increased in the Cur 8 group. The mRNA expression of TNF-α and IL-6 in the wound tissues of the Cur 8 group was less than those in the model group, while the expression of IL-10, VEGF-α and TGF-β was higher than those in the model group (P＜0.05). The expression of VEGF-α, TGF-β and p-Stat3 in Cur 8 group was higher than those in model group (P＜0.05). Conclusions Curcumin administration can alleviate DTPI of mice induced by ischemia-reperfusion, and its mechanism may be related to the inhibition of inflammatory response and promotion of angiogenesis.